DINAMIKA PROKRASTINASI AKADEMIK MAHASISWA PGMI: STUDI PERSEPSI DI IAIN LANGSA - Wahyuni Wahyuni; Muhaini Muhaini; Dinda Oktavia (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2026)
Academic procrastination is a common problem in higher education and can impact the quality of student learning processes and outcomes. This study aims to analyze the dynamics of academic procrastination among students in the PGMI Study Program at IAIN Langsa, based on their perceptions of the learning process. The study employed a qualitative descriptive approach, with data collection techniques including observation, interviews, and documentation. Subjects were purposively selected, specifically students with a tendency to engage in academic procrastination. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that academic procrastination has become a common behavior among students, particularly in the form of persisting with assignments until the deadline approaches. The main factors influencing this behavior include low learning motivation, poor time management skills, and classroom learning dynamics. Furthermore, academic pressure, the learning environment, and interactions between lecturers and students also influence student engagement in completing academic assignments. Academic procrastination not only results in delayed assignment submissions and a decline in the quality of learning outcomes, but also causes stress, anxiety, and academic pressure among students. This study confirms that handling academic procrastination requires strengthening learning motivation, self-regulation, and a more interactive and supportive learning process.